«dovrebbe essere essenziale dire [ɲɔkki] e non [ɲɔtʃi]» - Scheitza, Jan; Visser, Judith (Educazione Linguistica Language Education, 2019)
In the teaching of Italian in Germany, grammar is nowadays considered as a tool that serves language acquisition, but that is subordinated to the communicative goals of the language lessons. Teachers have to take these as a starting point for their didactic decisions. However, decision procedures do not only depend on educational policy or scientific findings, but also on individual hypotheses of various types. Based on 31 interviews of (future) teachers of Italian (2016-17), the present study aims at analysing (future) teachers’ decision making considering the teaching of grammar. The results show that a dialect and migrant background can play a significant role for didactic decisions.